Profound bilateral visual loss after hysterectomy indicated for severe postpartum haemorrhage. (6th January 2014) - Ostri, Christoffer; Zibrandtsen, Nathalie; Larsen, Michael; Hamann, Steffen
Abstract : We present a case of a patient with bilateral posterior ischaemic optic neuropathy in the previously unreported setting of hysterectomy indicated for severe postpartum haemorrhage. The diagnosis was based on clinical and paraclinical examinations, including MRI of the head, electroretinography (ERG) and visual evoked potentials (VEP) testing. During 1 year of follow-up, repeated optical coherence tomography (OCT) scans demonstrated optic disc atrophy, which was interpreted as a sign of direct retrograde ganglion cell degeneration after ischaemic damage to the retrolaminar part of the optic nerves. The diagnosis of perioperative posterior ischaemic optic neuropathy is mostly a clinical diagnosis. However, MRI plays a major role in excluding other causes of visual loss, and VEP, ERG and OCT are valuable supplemental diagnostic tools.